The First Touch of CSO: The Role of Sant’Egidio, Humanitarian Dialogue, and Muhammadiyah on Conflict Resolution - Mahdi, Imam (Universitas Muhammadiyah Yogyakarta, 2025)
Civil Society Organization (CSO) involvement in conflict resolution remains necessary. According to the qualitative research on three CSOs, when they first dealt with conflict, they were creative in resolving conflicts by sheltering communities from violence, fostering cohesion between competing parties, and having dialogue at the local and national levels. CSOs have attempted to maximize their potential and networks for negotiations to end in a peace treaty. Unfortunately, not all CSOs could carry out this mission due to restricted resources and competencies. This study unveiled that the success of CSOs in conflict resolution still required the state’s involvement as a source of pressure on the disputing parties and rooted support from civil society.